P-018 The North American Intracranial Stent Registry (NAISR) and unruptured aneurysm repair with the pipeline embolization device: using thromboelastography to screen for clopidogrel non-response and anti-platelet medication compliance. (4th July 2012) - McTaggart, R; Santarelli, J; Marcellus, M; Steinberg, G; Dodd, R; Do, H; Marks, M
Abstract : Introduction: The Pipeline Embolization Device (PED) results in greater metal coverage compared with other intracranial aneurysm stents. The optimal management of anti-platelet therapy has not been well defined. We perform platelet function testing using thromboelastography (TEG) to tailor anti-platelet induction and maintenance strategy in order to identify clopidogrel non-response and minimize thromboembolic complications. We introduce the North American Intracranial Stent Registry (NAISR) and report our experience with the PED with particular emphasis on our anti-platelet strategy and associated thromboembolic and hemorrhagic complication rates. Methods: Aneurysm repair with the PED was undertaken in 15 patients between October 6, 2009 and December 15, 2011. Two patients were treated prior to PED FDA approval and our use of TEG to screen for Clopidogrel non-responders. TEG screening was performed pre-procedure in 13 patients. In patients treated after TEG screening, we aimed for >40% ADP-induced inhibition with the P2Y12 inhibitors (Clopidogrel or Prasugrel); % Arachnidonic-Acid (AA) inhibition was tested as a medication (aspirin) compliance monitor. Platelet inhibition to ADP- and AA- agonists were calculated using commercially available TEG (HAEMONETICS®). The NAISR is a secure, web application which has been customized and specifically designed to allow multiple users/institutions elucidate what benefit, if any, platelet function testing has for patients being treated with intracranial stents. The NAISR is protected by Secure Socket Layer (SSL) encryption, a strong web based authentication system, and is supported by the Stanford Center for Clinical Informatics. Results: All patients were female (age 46–85). All aneurysms were >10 mm and fourteen (93%) aneurysms were in the anterior circulation. Five (33%) patients required >1 PED. All patients were treated with anti-platelet drugs (Plavix and Aspirin) before the procedure. Of the patients treated after TEG screening (n=13), we achieved target ADP-induced inhibition with Clopidogrel in nine and four patients (31%) required Prasugrel, which was started post-procedure. We found % AA inhibition a useful aspirin compliance index as 12/13 (92%) patients achieved >90% inhibition as inpatients vs 8/13 (61%) while pre-procedure outpatients. Thromboembolic complications occurred in two patients (one prior to TEG screening and one after TEG screening was initiated). The thromboembolic complication after TEG screening was intraprocedure in-stent thrombus formation which responded to Integrilin in a Clopidogrel non-responder (low ADP-induced inhibition on the immediate pre-procedure TEG). The patient had no permanent deficits and was transitioned to Prasurgel post-procedure. There were no hemorrhagic complications in any patient. Conclusions: In our series of PED patients using the TEG screening and anti-platelet strategy described, there was one thromboembolic complication in a patient with low inhibition by TEG. As this is a small, single-institution series we are unable to determine what benefit our anti-platelet strategy has in PED patients. We feel the NAISR offers the SNIS membership an opportunity to elucidate the benefit or risk of screening for Clopidogrel non-response; NAISR will determine if aggressive anti-platelet regimens reduce thromboembolic complications and/or increase bleeding complications or even delay aneurysm thrombosis. Competing interests: None.